2016
DOI: 10.1210/en.2015-2078
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Exerts Neurotrophic Effects on Dendritic Arborization, Spinogenesis, and Neurogenesis of the Dentate Gyrus of Male Mice

Abstract: The hippocampus, a brain region critical for learning, memory and emotional processing, maintains its capacity to undergo structural plasticity throughout life. Hippocampal structural plasticity can be modulated by a number of intrinsic and extrinsic factors. This study investigated the effects of adiponectin, an adipocyte-derived hormone, on dendritic growth, arborization, and spinogenesis in mature granule neurons of the hippocampal dentate gyrus generated during embryonic (early-born) or early postnatal (la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 123 publications
1
82
0
Order By: Relevance
“…Adiponectin enters the brain from circulation and directly targets neurons (Ng and Chan 2017; Thundyil et al 2012; D. Zhang et al 2016; Zhang et al 2017; Song et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin enters the brain from circulation and directly targets neurons (Ng and Chan 2017; Thundyil et al 2012; D. Zhang et al 2016; Zhang et al 2017; Song et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have focused on its neuroprotective functions and have tried to reveal its detailed mechanisms. A recent study showed that APN can exert neurotrophic effects and neurogenesis in the dentate gyrus in male mice and suggests that APN plays an important role in hippocampal structural plasticity [39]. This indicates that exogenous APN supplements may be useful to improve hippocampal or neurological defects caused by ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it increases anti-inflammatory cytokines such as IL-10 in the macrophage (Moschen et al 2012) and has beneficial effects on cardiovascular function (Han et al 2007;Wang et al 2009). In addition, adiponectin can enhance adult hippocampal neurogenesis in mice and in cell culture models (Zhang et al 2011, 2016). Accordingly, Yau et al (2014) suggest that adiponectin can cross the blood–brain barrier and that increased adiponectin levels may modulate hippocampal neurogenesis and ameliorate mood.…”
Section: Peripheral Organs and Brain Functionmentioning
confidence: 99%